E-commerce Platform Performance, Digital Marketing and Supply Chain Capabilities - Agus, Anna Amalyah; Yudoko, Gatot; Mulyono, Nur Budi; Imaniya, Taliya (Universitas Prasetiya Mulya, 2020)
By using Indonesian case studies, this research plan to fill the research gap in the theories of transaction cost economics, multi-attribute utility theory, agency theory and information-processing theory, through variable based modeling. For business and industry stakeholder point of view, this research is expected to be useful for Indonesian e-commerce platform ecosystem stakeholders especially regulators, to give insights towards dynamics within e-commerce platform ecosystem. This paper originality lies on proposing e-commerce conceptual model by using multidisciplinary approach through combining four main constructs, which consists of relative e-commerce platform performance, digital promotion capability, customer experience review rating and supply chain capabilities. The model also accommodates seasonal pricing and logistic outsourcing as intervening variables to examine model sensitivity. With sample size of 1288 people who have purchased items in at least two e-commerce platform, collected data is processed using Structural Equation Modeling (SEM) method by LISREL software.